Acceptance and use of cloud-based virtual platforms by higher education vocational school students: application of the UTAUT model with a PLS-SEM approach - Can Sayginer (Innoeduca, 2023)
Cloud-based virtual platforms emerged as a new way of tracking lectures as mobile, reliable, and productive. Especially due to the COVID-19 breakdown, they became popular because checking the students’ effort, performance, social interaction among each other, and the condition of vocational schools was easy to track during and after the online classes. The research aims to analyze the behavioral intention to adopt cloud-based virtual platforms such as Blackboard, Microsoft, Zoom, Edmodo, Sakai and Moodle during COVID-19. 14 questions were asked to 313 students from higher education vocational schools in the district of Izmir, Turkey via Google Forms. PLS-SEM analyses were made by SmartPLS 4.0 software and by proposing the Unified theory of acceptance and use of technology (UTAUT) theory. The results showed that the variance of effort expectancy, behavioral intention, and facilitating conditions explained 76.00% of the proposed model. The research contributes to understanding the students’ behavior toward the acceptance of cloud-based virtual platforms in case of new variants or other epidemic diseases emerged in the future.